ETOS KERJA DALAM PERSPEKTIF ISLAM - Nasution, Mhd Thoib (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2017)
The work ethic should be based on three elements, monotheism, piety, and worship. Tawheed would encourage that work and the work is a means to download Tauhidkan Allah SWT. so avoid the cult of material. The work ethic in the broad sense of moral concerns in employment. To be able to weigh how a person's character in the work depends on how workers see the value of work in life, how to work and the nature of work.